Acoustic emission monitoring for leak detection in pressurized tank - Rina, Ahmad (Universiti Malaysia Sarawak, (UNIMAS), 2006)
Leak testing is the measurement of the amount of fluid leaking through material over a given time, at a given pressure. In this project, acoustic emission method is used to study the behaviour of the air leakage in the tank by monitoring on controlled leaks. Small drilled holes are built in the tank to represent as the leak point due to crack. Air was compressed into the tank using air-compressor at certain pressure. Testing was performed for non-leaking and leaking condition. Acoustic emission is a sound that is generated by defects within the materials such as plastic deformation, crack initiation or growth. AE sensor was detecting the signal from the pressurized tank and transmits the electrical signal to the computer for analyzing the acoustic emission activity. The leak detection project has been successful performed and has the ability to detect and analyze the behaviour of acoustic emission signals result by the air leakage. Found that the wave graph of leaked air is increased if having the high pressure and bigger leak diameter. The furthest the sensor placed from the leak hole, the smallest wave found in the graph.